Preparation process of high-performance concrete prefabricated component

By combining step-by-step mixing, vacuum extraction, and intelligent curing cover, the problems of poor mixing homogeneity and stress concentration during demolding in the preparation of high-performance precast concrete components are solved, achieving an efficient and non-destructive preparation process and improving the strength and durability of the components.

CN121062014AInactive Publication Date: 2025-12-05FUJIAN JIANHAO CONSTR TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511352870.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-22
Publication Date
2025-12-05
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing high-performance concrete precast component preparation processes suffer from problems such as poor mixing homogeneity, incomplete air bubble removal, rough curing process, and reliance on experience, which limit the improvement of component quality and easily lead to stress concentration and edge damage during demolding.

Method used

Stepwise stirring technology ensures efficient adsorption of water-reducing agent and precise and stable water-binder ratio. Air bubbles are eliminated through the synergistic effect of vacuum pumping and energy field viscosity reduction. Combined with intelligent curing cover, the system dynamically responds to the hydration state, providing on-demand energy supply and oscillation enhancement. During demolding, pulsed airflow forms an air cushion to achieve non-destructive and flexible demolding.

Benefits of technology

It significantly improves the homogeneity and strength of concrete, protects the integrity of the edges and corners of components, increases the yield and quality stability of precast components, and realizes resource recycling and production efficiency improvement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121062014A_ABST
    Figure CN121062014A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation process of a high-performance concrete prefabricated part, and relates to the technical field of constructional engineering. Comprising the following steps: preparing raw materials: weighing a solid waste-based cementing material, recycled aggregate, fibers, a water reducing agent and mixing water according to a mixing ratio, and pretreating the raw materials; preparing a mold: manufacturing a mold base body according to the design drawing of the prefabricated part, and uniformly coating a polytetrachloroethylene composite coating; and the embedded part is additionally installed and fixed, and the mold is closed and locked. Through step-by-step stirring, efficient adsorption of the water reducing agent and accurate and stable water-binder ratio are ensured, formation of initial defects is reduced, and the homogeneity of concrete is enhanced; the hydration state is dynamically responded through the intelligent maintenance cover, energy is supplied according to needs, stress damage is avoided, the microstructure is optimized, and the quality of the prefabricated part is improved; all locking force is released firstly, then an air cushion is formed through pulse airflow, lossless flexible demolding is achieved, the integrity of corners of the prefabricated parts is protected, and the yield of the prefabricated parts is greatly increased.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of building engineering, in particular to a preparation process of high-performance concrete prefabricated components. BACKGROUND

[0002] The high-performance concrete prefabricated component is a core support of modern building industrialization, is widely used in prefabricated buildings, bridges, underground pipe galleries and other key fields with extremely high performance requirements due to its excellent strength, durability and high quality and high efficiency advantages brought by factory production, and is a strategic product for promoting the transformation and upgrading of the building industry. However, the conventional preparation process still has significant bottlenecks, mainly in poor mixing homogeneity, incomplete bubble discharge, extensive curing process and dependence on experience, which seriously restricts the further improvement of the component quality.

[0003] For example, the patent with the publication number CN120116318A discloses a manufacturing process of high-performance concrete prefabricated components, which comprises the key steps of raw material preparation, mixing, vibration forming, steam curing, demolding and stacking. The double-shaft forced mixer is used to ensure the uniformity of the concrete slurry; the high-frequency vibrator is used to eliminate bubbles and improve the compactness of the component; the steam curing is combined to accelerate the concrete hardening process and improve the early strength; and the hydraulic jacking device is used to optimize the demolding efficiency. The manufacturing process effectively improves the quality stability of the prefabricated component, significantly enhances the production efficiency and reduces the manufacturing cost.

[0004] However, the above technical solution still has the following deficiencies: 1. One-time extensive feeding, the aggregate can instantaneously absorb a large amount of water, which may cause imbalance of water-binder ratio and uneven distribution of water reducing agent, resulting in poor concrete homogeneity; 2. Fixed and programmed steam curing, without attention to the actual hydration state of the concrete, stress cracks are easily generated and the strength is damaged; 3. The hydraulic jacking demolding method may cause stress concentration of the component due to the influence of adhesion and vacuum adsorption force at the demolding moment, resulting in damage of the component edges and corners or internal micro-cracks. SUMMARY

[0005] The application aims to provide a preparation process of high-performance concrete prefabricated components to solve the problems in the background art.

[0006] To achieve the above-mentioned purpose, the application provides the following technical solution: a preparation process of high-performance concrete prefabricated components, comprising:

[0007] Raw material preparation: weighing the solid waste-based cementitious material, recycled aggregate, fiber, water reducing agent and mixing water according to the mixing ratio, and pretreating the raw materials;

[0008] Mold preparation: according to the prefabricated component design drawing, the mold base is made, and the polytetrafluoroethylene composite coating is evenly coated; the embedded parts are installed and fixed, and the mold is closed and locked;

[0009] Stirring and quality control: prepare homogeneous slurry and wet aggregate base, inject the slurry into the wet aggregate base, homogenize to obtain concrete mixture, and test the performance of the concrete mixture;

[0010] Pouring: inject the concrete mixture into the mold, and extrude, scrape and recycle the excess material by the profiling press plate to obtain the component embryo;

[0011] Curing: dynamically respond to the state of the concrete hydration reaction through the intelligent curing cover, and perform on-demand energy supply, oscillation strengthening and closed-loop drying to obtain the base component;

[0012] Demolding and trimming: demold the base component, perform online visual scanning on the base component during hoisting, obtain defect data, and perform automatic trimming to obtain the prefabricated component;

[0013] Quality verification and storage: perform compressive strength test and durability test on the prefabricated component, and intelligently store the prefabricated component that passes the verification.

[0014] Further, the method for pretreating the raw materials comprises:

[0015] Microwave-chemical combined impurity removal and microbial mineralization repair are performed on the recycled aggregate;

[0016] Magnetic field pre-orientation arrangement and plasma oil removal and roughening are performed on the fibers;

[0017] Solid waste-based cementitious materials are subjected to collaborative thermalization and counter-current chromatography to enrich key components.

[0018] Further, the contents of the mold preparation step include:

[0019] A mold base integrating a magnetic positioning unit, a self-sealing groove and an optical calibration base point is made, and a vacuum micropore array is processed on the working surface of the mold base;

[0020] Based on the physical mask method, the polytetrafluoroethylene composite coating is selectively sintered on the working surface, and the physical mask is removed after the coating is cooled and solidified;

[0021] The mold is cleaned, and the surface state of the polytetrafluoroethylene composite coating and the mold size are automatically scanned, and whether the vacuum micropore array is unblocked is checked;

[0022] The embedded parts are placed in the magnetic grid and automatically adsorbed and locked by magnetic force;

[0023] The mold is closed, the locking mechanism triggers the expansion of the sealing strip in the self-sealing groove to achieve self-sealing, automatically reads the optical reference point to check the closing accuracy, performs vacuum test to check the sealing integrity, and obtains the mold finished product.

[0024] Further, the stirring and quality control step includes:

[0025] The solid waste-based gel material, the water reducing agent, and part of the water are subjected to high-speed shearing stirring to obtain a homogeneous slurry;

[0026] The recycled aggregate and the remaining water are stirred to obtain a uniform wet aggregate bed;

[0027] The slurry is injected into the stirring wet aggregate bed by means of pressurized injection;

[0028] After all the homogeneous slurry is injected into the wet aggregate bed, short-time high-efficiency homogenization stirring is performed to obtain a concrete mixture with uniform distribution of components;

[0029] The concrete mixture is subjected to slump test and bulk density test, and the process is adjusted according to the test results.

[0030] Further, the content of the pouring step includes:

[0031] The concrete mixture is injected through a movable nozzle, tightly fills the surface, and is uniformly injected at a preset speed along a preset path, and fibers are added; at the same time, a directional energy field is applied above the filling surface to reduce the apparent viscosity of the concrete, and a vacuum is applied in the micropores of the side wall area of the mold that has not been filled to discharge the internal bubbles of the concrete;

[0032] The filling height in the mold is monitored in real time, and the injection is stopped when the preset filling height is reached; an intelligent pressing plate with a profiling structure is used to extrude and flatten the surface to the design elevation, and the excess material is cut off and recycled;

[0033] The vacuum state is maintained, the vacuum degree change is monitored, the internal structure is confirmed to be stable, and the surface is automatically scanned to confirm that there is no bleeding phenomenon and no bubble overflow, and a component embryo is obtained.

[0034] Further, the vacuum applied in the micropores of the side wall area of the mold that has not been filled is linked with the position of the movable nozzle, so that the vacuum always acts on the front of the gas-material interface.

[0035] Further, the content of the curing step includes:

[0036] An enclosed intelligent curing cover is covered on the component embryo, and initial static stopping is performed;

[0037] The core temperature and humidity of the component embryo are monitored in real time, and the directional energy supply is dynamically started.

[0038] When the core temperature reaches the preset value and tends to be stable, a temperature oscillation cycle is adopted to optimize the microstructure inside the component embryo and obtain early strength;

[0039] According to real-time humidity data, the drying mode is automatically switched until the internal humidity of the component embryo is balanced with the external environment, and the base component is obtained.

[0040] Further, the contents of the demolding and trimming step include:

[0041] The magnetic force of all magnetic unit positioning units is cut off, the locking mechanism automatically releases the mechanical locking force according to the preset unlocking sequence, and sends a reverse signal to the micro-porous sealing strip to trigger the initial demolding;

[0042] The lifting appliance adsorbs the surface of the base component by negative pressure adsorption, and the micro-porous array of the mold side wall sprays pulse airflow, and the base component is lifted away from the mold;

[0043] During the process of lifting the base component away from the mold, the type, size and three-dimensional coordinates of the base component defects are automatically identified and labeled through online visual scanning and comparison, and automatic trimming is performed accordingly to obtain the prefabricated component.

[0044] Further, the contents of the quality verification and storage step include:

[0045] The dynamic response signal of the prefabricated component is monitored in real time, the uniformity and activity of the internal structure change are analyzed, and the compressive strength of the prefabricated component is calculated;

[0046] The surface of the prefabricated component is scanned, the difficulty of water molecules entering the surface layer of the prefabricated component is evaluated, and a permeability index is obtained; the permeability index is compared with the predicted value of the key durability index to obtain durability evaluation data;

[0047] The prefabricated component that passes the quality verification is stored in a three-dimensional storage location provided with an adaptive support table; information management is performed through an electronic tag, and the prefabricated component is automatically stored and taken out vertically according to instructions.

[0048] Compared with the prior art, the beneficial effects of the present application are:

[0049] A high-performance concrete prefabricated component preparation process upgrades the performance of recycled raw materials through physical, chemical and biological technologies, converts construction waste and industrial solid waste into high-quality raw materials for preparing high-performance concrete, reduces the risk of land occupation and environmental pollution, and realizes resource recycling; through the triple synergistic effect of bottom injection, vacuum air pumping and energy field viscosity reduction, active and efficient bubble removal is realized, a component with dense internal structure is obtained, and the strength and durability of the component are significantly improved.

[0050] Meanwhile, step-by-step mixing ensures efficient adsorption of water-reducing agents, precise and stable water-cement ratio, reduces the formation of initial defects, and enhances the homogeneity of concrete; intelligent curing cover dynamically responds to the hydration state and supplies energy as needed, avoiding stress damage, optimizing microstructure, and improving the quality of precast components; by first releasing all locking forces and then forming an air cushion through pulsed airflow, non-destructive flexible demolding is achieved, protecting the integrity of the edges and corners of precast components and greatly improving the yield of precast components. Attached Figure Description

[0051] Figure 1 This is a schematic diagram of the manufacturing process of the high-performance precast concrete components of the present invention;

[0052] Figure 2 This is a schematic diagram of the mold manufacturing method of the present invention;

[0053] Figure 3 This is a schematic diagram of the stirring and quality control method of the present invention;

[0054] Figure 4 This is a schematic diagram of the casting method of the present invention;

[0055] Figure 5 This is a schematic diagram of the maintenance method of the present invention;

[0056] Figure 6 This is a schematic diagram of the demolding and trimming method of the present invention;

[0057] Figure 7 This is a schematic diagram of the quality verification and storage method of the present invention. Detailed Implementation

[0058] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0059] like Figure 1 As shown, the present invention provides a technical solution: a process for preparing high-performance precast concrete components, comprising:

[0060] Raw material preparation: Weigh solid waste-based cementitious materials, recycled aggregates, fibers, water-reducing agents and mixing water according to the mixing ratio, and pre-treat the raw materials.

[0061] It is important to note that the raw materials should be weighed accurately according to the mixing ratio, such as 700 kg / m³ for solid waste-based gel materials. 3 200kg / m³ of recycled coarse aggregate (5-10mm) 3, recycled fine aggregate (0-5mm) 600kg / m 3 , fiber (such as steel fiber) 150kg / m 3 , water reducing agent (such as polycarboxylic acid water reducing agent) 14kg / m 3 , mixing water 140kg / m 3 ; the steel fiber has a length of 12mm and an aspect ratio of 50; the polycarboxylic acid water reducing agent has a solid content of about 30% and a water-reducing rate of ≥35%.

[0062] The method for pretreating raw materials includes: for recycled aggregate, soaking the recycled aggregate in a specific weak acid (such as dilute acetic acid) or chelating agent solution to soften, dissolve or loosen old cement products attached to the surface of the aggregate; after chemical soaking, microwave irradiation is performed on the aggregate, the internal heating effect of the microwave instantaneously generates heat in the aggregate and its internal and surface moisture, causes the softened old paste to crack and peel off, and accelerates the progress of the chemical reaction, thereby improving the efficiency of impurity removal; after impurity removal, the aggregate is soaked in a solution containing specific microorganisms (such as Bacillus pasteurii) and nutrient solution (urea, calcium source, etc.), the microorganisms metabolize and decompose to generate calcium carbonate, thereby repairing the internal cracks of the recycled aggregate, improving its density and strength, and reducing the porosity of the aggregate.

[0063] For steel fiber, low-temperature plasma is used to bombard and decompose the oil film on the surface of the steel fiber, and at the same time, a micron-level rough and uneven rubbing structure is formed, which greatly improves the mechanical engagement force and chemical bonding force of the steel fiber with concrete; the steel fiber is then dispersed through a strong magnetic field area, and under the action of the magnetic field, the steel fiber is quickly arranged in order along the direction of the magnetic force lines; the steel fiber is synchronously added during subsequent concrete pouring into the mold.

[0064] For solid waste-based gel materials, a plurality of industrial solid wastes are mixed at an optimal mixing ratio, and then heat-treated at a certain temperature, which is usually lower than the traditional cement sintering temperature, to stimulate the potential cementitious activity of the plurality of solid wastes; the heat-treated solid waste materials are then made into a solution or suspension, injected into a countercurrent chromatography system, and the key ingredients with the highest cementitious activity are separated and purified from the complex solid waste mixture, and the inert or harmful ingredients are removed, thereby obtaining a new green gel material with higher strength and better durability. The optimal mixing ratio can be obtained by theoretically analyzing the initial selection range of the solid waste components, then using experimental design method for efficient sampling, establishing a mathematical model of the ratio and performance, and finally solving by multi-objective optimization algorithm, and verified by experiments.

[0065] The recycled aggregate refers to granular material which can replace natural sandstone for preparing new concrete after processing and treatment such as crushing, screening and cleaning of construction waste; mainly comes from waste concrete produced by demolition of old buildings, bridges, roads and the like; realizes resource recycling, reduces mining of natural minerals, and reduces cleaning of construction waste.

[0066] Mold preparation: according to the prefabricated component design drawing, a mold base is made, and a polytetrafluoroethylene composite coating is uniformly applied; embedded parts are installed and fixed, and the mold is closed and locked.

[0067] As shown in Figure 2 The present application provides a mold manufacturing method;

[0068] Specifically:

[0069] The mold base integrated with a magnetic positioning unit, a self-sealing groove and an optical calibration base point is manufactured, and a vacuum micropore array is processed on the working surface of the mold base;

[0070] Based on the physical mask method, the polytetrafluoroethylene composite coating is selectively sintered on the working surface, and after the coating is cooled and solidified, the physical mask is removed;

[0071] The mold is cleaned, and the surface state of the polytetrafluoroethylene composite coating and the mold size are automatically scanned, and whether the vacuum micropore array is unblocked and free from blockage is checked;

[0072] The embedded part is placed in the magnetic grid, and it is automatically adsorbed and locked by magnetic force;

[0073] The mold is closed, the sealing strip in the self-sealing groove is expanded to realize self-sealing by triggering the locking mechanism, the optical reference point is automatically read to check the closing precision, the sealing integrity is tested by vacuum pumping test, and the mold finished product is obtained.

[0074] It should be noted that according to the CAD design drawings, the base body of the mold is machined using a high-precision numerical control machine tool (CNC), and the mold material is usually invar, aluminum alloy or high-strength composite material; while machining the mold base, mounting grooves are machined at predetermined positions (such as edges, parting surfaces), and electromagnet units are fixed therein for subsequent precise adsorption and fixation of embedded parts; on the parting surface of the mold, a continuous groove with a specific cross-sectional shape is machined by CNC milling for placing a sealing strip; at key positions on the non-working surface of the mold, high-precision recesses or mounting holes are machined by CNC, and optical target balls made of glass or ceramic are embedded; on the working surface of the mold, a plurality of micron-level holes are machined using a pulse laser drilling machine, which are connected to the pre-processed vacuum pipeline network inside the mold for subsequent vacuum pouring to remove bubbles and compact the layers. The vacuum pipeline network is divided into multiple independent controllable areas, each with an independent vacuum valve and sensor.

[0075] According to the position of the area that does not require coating, such as the vacuum micro-hole, a corresponding protective cover, i.e. a physical mask, is cut on the metal sheet using a laser cutting machine; the prepared physical mask is accurately covered on the working surface of the mold to ensure that the area that needs protection is completely covered, while the area that needs coating is exposed. Then, the polytetrafluoroethylene (PTFE) composite coating is applied to the exposed mold surface by spraying; and the mold is heated in a controllable sintering furnace, with the temperature accurately controlled above the melting point of PTFE, so that it melts, levels and solidifies to form a smooth, dense and low-surface-energy coating; after the coating cools and solidifies, the physical mask is removed.

[0076] Dust, debris and volatile substances that may be generated during the sintering process are completely removed from the mold surface using an industrial vacuum cleaner. Then, a non-contact surface topography measuring instrument (such as a white light interferometer) is used to check the thickness, uniformity and presence of defects such as scratches, bubbles and particles of the coating; a structured light three-dimensional scanner is used to scan the mold in full size, and the obtained point cloud data is compared with the original CAD model to verify the machining accuracy, especially the tolerance of the key surface. Then, a vacuum pump is connected to the vacuum interface of the mold and vacuumized, while an ultrasonic detector is moved on the surface of the surface to listen, confirming that all the micro-holes are unobstructed.

[0077] According to the design drawings, the embedded part wrapped with magnetic material is preliminarily placed at the approximate position on the mold surface; the placement position of the embedded part is confirmed by visual recognition, the magnetic force is enhanced, and the embedded part is adsorbed and fixed on the predetermined magnetic grid positioning point. The magnetic grid is defined by the position of the electromagnet embedded in the mold.

[0078] The upper mold is accurately aligned and closed with the lower mold using an automatic mold closing machine, and then pressure is applied by a locking mechanism (such as a hydraulic clamp) to extrude the rubber sealing strip in the self-sealing groove, so that it deforms and expands to tightly fill the small gap of the parting surface, thereby achieving sealing. After the mold is closed, a laser tracker automatically scans the optical target balls in the mold, and by comparing the actual relative positions of these optical target balls with the theoretical positions during mold design, the closing accuracy data such as parallelism and misalignment amount are obtained. Then, a vacuum test is performed to judge the integrity of the sealing by monitoring the rate of decline of the vacuum degree.

[0079] Stirring and quality control: preparing homogeneous slurry and wet aggregate base, injecting the slurry into the wet aggregate base, homogenizing to obtain concrete mixture, and testing the performance of the concrete mixture.

[0080] As shown in Figure 3 , the present application provides a stirring and quality control method;

[0081] Specifically:

[0082] The solid waste-based gel material, the water reducing agent, and part of the water are subjected to high-speed shearing stirring to obtain a homogeneous slurry;

[0083] The recycled aggregate and the remaining water are stirred to obtain a uniform wet aggregate base;

[0084] The slurry is injected into the stirring wet aggregate base by means of pressurized injection;

[0085] After all the homogeneous slurry is injected into the wet aggregate base, short-time high-efficiency homogenization stirring is performed to obtain a concrete mixture with uniform distribution of components;

[0086] The concrete mixture is subjected to slump test and unit weight test, and the process is adjusted according to the test results.

[0087] It should be noted that according to the designed proportioning, the accurately measured and pretreated solid waste-based cementitious material, the polycarboxylate superplasticizer, and part of the mixing water (80% of the total water amount) are put into a high-speed shearing stirrer for short-time stirring to break up the cementitious material particle agglomerates and make the polycarboxylate superplasticizer molecules quickly and uniformly adsorbed to the surface of each cementitious material particle, fully releasing the water-reducing effect, thereby obtaining a slurry with good fluidity, no clumping, and highly uniform composition.

[0088] The accurately measured and pretreated recycled aggregate and the remaining mixing water are put into a forced stirrer (such as a horizontal shaft stirrer) for stirring at a medium-low speed to fully wet the aggregate particles with water, thereby obtaining a moist and uniform aggregate mixture, i.e., a wet aggregate base, effectively preventing the dry aggregate from instantaneously absorbing too much water when mixed with the slurry in the subsequent process, thereby stabilizing the water-cement ratio of the concrete mixture and ensuring the workability.

[0089] The prepared slurry is transported through a pipeline to a jet pump, and the slurry is injected into the tumbling wet aggregate bed at a certain pressure through several nozzles during low-speed stirring of the wet aggregate bed in the mixer. The nozzles can be fan-shaped or wide-angle conical nozzles to ensure that the injection covers a large and uniform area.

[0090] After all the slurry is injected into the wet aggregate bed, the stirring speed of the mixer is appropriately increased, and rapid stirring is performed for a short time (1-2 minutes) to finely adjust the aggregate that has been preliminarily wrapped and the slurry, so as to ensure that the slurry is fully filled between the aggregates, and large bubbles are discharged, so that a completely uniform and color-uniform concrete mixture is formed.

[0091] A representative sample is taken from the same batch of mixed concrete, the concrete is filled into a standard slump cone in three layers, each layer is inserted and tamped 25 times, and after being smoothed, the height difference of the concrete slump is measured, and the fluidity of the concrete is evaluated. The concrete mixture is filled into a standard capacity cylinder with a known volume, weighed and calculated for unit volume mass. If the slump is lower than the threshold value (120-200 mm), it may be due to insufficient water, insufficient polycarboxylate superplasticizer, or high aggregate water absorption rate; the adjustment method is: while keeping the water-binder ratio unchanged, slightly increase the water and polycarboxylate superplasticizer at the same time, for example, add 0.5 kg / m 3 For increment, retest after stirring for 1 minute again; attention should be paid to not adding water alone, otherwise the strength will be reduced. If the slump is higher than the threshold value, it may be due to excessive water or polycarboxylate superplasticizer; the adjustment method is: add a small amount of cementitious material and aggregate according to the design proportion, retest after stirring for 1 minute again. If the apparent density is abnormal, it may be due to incorrect raw material metering or uneven stirring; the adjustment method is: immediately check the calibration record of the mixer metering system, and confirm whether the stirring time is sufficient. The representative sample is taken through a special sampling port in the delivery pipeline: first open the valve and discharge a part of the concrete that flows out first, because this part may be the material retained in the inner wall of the pipeline wall; then use a container to take the concrete that stably flows out afterwards, until the required amount is obtained, and this part of the concrete directly represents the material state about to be poured, so that a representative sample can be obtained.

[0092] Pouring: the concrete mixture is injected into a mold, and is extruded, smoothed and the excess material is recycled by a profiled pressing plate, so as to obtain a component embryo.

[0093] As shown in Figure 4 , the application provides a pouring method;

[0094] Specifically:

[0095] The concrete mixture is injected through a movable nozzle, closely filling the surface and at a uniform speed along a preset path, and the fibers are added; at the same time, a directional energy field is applied above the filling surface to reduce the apparent viscosity of the concrete, and a vacuum is applied in the micro-holes of the side wall area of the mold that has not been filled to expel the internal bubbles of the concrete;

[0096] The filling height in the mold is monitored in real time, and the injection is stopped when the preset filling height is reached; a smart press plate with a profiling structure is used to extrude and flatten the surface to the design elevation, while the excess material is cut off and recycled;

[0097] The vacuum state is maintained, the vacuum degree is monitored, the internal structure is confirmed to be stable, and the surface is automatically scanned to confirm that there is no bleeding phenomenon and no bubble overflow, obtaining the component embryo.

[0098] It should be noted that while the concrete mixture is injected into the mold, the directionally arranged steel fibers flow is simultaneously sprayed into the flowing concrete flow from another nozzle under the blowing of compressed air; the process needs to control the flow rate of the concrete and the speed and angle of the steel fiber injection, so that the flow force field of the concrete and the directional direction of the steel fiber are coordinated, so that the steel fiber can maintain its original directional arrangement state to the maximum extent after entering the mold before the concrete solidifies.

[0099] The movable nozzle is controlled by a mechanical arm. During the movement of the nozzle, the nozzle is always close to the lowest surface of the area to be filled, so as to avoid the air introduced by the falling of the concrete mixture from a high place. The nozzle moves at a uniform speed according to a preset path plan, and the concrete mixture is smoothly injected into the mold cavity. At the same time, the steel fibers arranged in the direction are synchronously injected into the flowing concrete flow under the blowing of compressed air. The flow speed of the concrete, the speed and angle of the steel fiber injection, the flow force field of the concrete and the directional direction of the steel fiber are controlled, so that the steel fiber can maintain the original directional arrangement state to the maximum extent after entering the mold and before the concrete solidifies. An array of high-frequency vibrators is installed above the mold, and the energy field is applied above the filled surface of the concrete. The energy is transmitted to the newly injected concrete, the apparent thixotropy and yield stress of the concrete are reduced through high-frequency micro-vibration, the flowability of the concrete is instantaneously enhanced, so that the bubbles are more easily floated and separated, and the concrete is smoothly filled in the complex corner. The central control system tracks the accurate position of the movable nozzle in real time, and applies vacuum (such as -0.09Mpa) in the micro-pores of the side wall area of the mold which has not been filled, so that the vacuum always acts on the air-material interface front. When the area is filled with concrete, the vacuum degree of the area is adjusted to a lower, stable maintenance vacuum degree (such as -0.02Mpa), to help the preliminary stabilization. In addition, when about 1 / 3 of the design height of the concrete is injected, the injection is paused, a wireless temperature and humidity sensor is placed at the center position of the surface of the concrete slurry being poured, and the subsequent concrete pouring process is continued. The concrete poured subsequently completely covers and wraps the sensor, ensuring that the sensor is finally located at the internal core position of the prefabricated component.

[0100] A non-contact laser ranging sensor is vertically directed to the inside of the mold to measure the liquid level of multiple points in the mold in real time, and the data is sent to the central control system. When the average height of the liquid level reaches the preset filling height (considering the subsequent troweling allowance), the central control system sends a command to stop injection. Then, a mechanical arm controls a profiling press plate to vertically extrude the concrete surface with a preset force (such as 100N / m 2 ), further expels the internal residual bubbles, and ensures that the concrete is completely dense, avoiding that the concrete does not fill the top corner of the mold. Subsequently, the mechanical arm moves the profiling press plate according to a preset three-dimensional path completely consistent with the design surface of the component, at a constant speed and height, to scrape off the excess concrete higher than the design elevation; at the same time, a rotary scraper installed in the advancing direction of the profiling press plate timely collects the excess concrete scraped off and transports it back to the mixing station through a pipeline, realizing green recycling of materials. The profiling press plate has a lower surface shape completely consistent with the upper surface shape of the prefabricated component design, and integrates a force sensor and a high-precision displacement sensor.

[0101] After the screeding is completed, the vacuum inside the mold is maintained for a period of time (e.g., 10 minutes) to expel the very small bubbles remaining inside the concrete and to inhibit water evaporation, eliminating surface weeping. During the entire period of rest, the vacuum level of the sealed mold cavity is continuously monitored. If the vacuum level curve remains very stable, it indicates that the internal structure of the concrete has stabilized and no gas continues to escape. If the vacuum level continues to drop significantly, it indicates that there may be a leak or that the concrete is still generating bubbles, and the rest time needs to be extended. After the vacuum level of the sealed mold cavity stabilizes, the surface is automatically scanned using a laser surface scanner. The presence of a water film is determined by analyzing the uniformity of the surface image, and any surface breakage bubbles or depressions are identified by 3D topography scanning. When the vacuum level curve is stable and the surface scan is defect-free, a high-quality component embryo is obtained, ready for the curing stage.

[0102] Curing: The intelligent curing cover dynamically responds to the state of the concrete hydration reaction, and performs on-demand energy supply, oscillation reinforcement, and closed-loop drying to obtain a base component.

[0103] As shown in Figure 5 , the present application provides a curing method;

[0104] Specifically:

[0105] An enclosed intelligent curing cover is applied to the component embryo, and initial static stopping is performed;

[0106] The core temperature and humidity inside the component embryo are monitored in real time, and directional energy supply is dynamically started;

[0107] When the core temperature reaches the preset value and tends to be stable, a temperature oscillation cycle is adopted to optimize the microstructure inside the component embryo and obtain early strength;

[0108] According to real-time humidity data, the drying mode is automatically switched until the humidity inside the component embryo is balanced with the outside environment, and a base component is obtained.

[0109] It should be noted that the intelligent curing cover is integrated with: a heating unit, such as uniformly distributed infrared heating pipes; a cooling unit, such as a circulating cooling liquid pipeline; a humidifying / drying unit, such as an ultrasonic humidifier; an oscillation energy unit, such as a variable frequency electromagnetic oscillator; and a sensor array, including temperature sensors, humidity sensors, and non-destructive strength monitors (such as ultrasonic propagation speed measurement devices).

[0110] Since the strength of concrete is extremely low before initial setting, it is prone to cracking if the surface moisture evaporates too quickly or the temperature difference between the inside and outside is too large. Therefore, after the curing cover is placed on the component embryo, the active temperature control is not started immediately, but the current environmental conditions are maintained to allow the concrete to rest for a period of time to obtain initial strength in a stable and undisturbed environment. The static rest time is not a fixed value, and the rate of change of the core temperature of the component is continuously monitored as the main basis for judgment. When a sustained and stable upward trend in the core temperature is monitored, indicating that the hydration reaction has accelerated and passed the initial setting point, the static rest period automatically ends. At the same time, the surface humidity is continuously monitored to ensure that it is above 95%, and if the humidity is insufficient, the humidification unit is automatically started to prevent plastic shrinkage cracking while maintaining the static rest state. For typical solid waste-based cementitious materials, the static rest time is usually 2-6 hours.

[0111] The core temperature, humidity inside the component embryo, and the external temperature, humidity are monitored in real time through the wireless temperature and humidity sensors embedded during the pouring process and the sensors of the curing cover itself. The microprocessor built into the curing cover analyzes the data according to the pre-set algorithm model (such as a prediction model based on mature hydration heat). When the monitored core temperature rise rate is lower than the ideal hydration curve, it is determined that the hydration reaction is slow, and the directional heating unit is automatically started, such as turning on the infrared heating in specific areas, to perform regional and gentle heating of the component to supplement the energy required for hydration and raise the concrete temperature to the optimal hydration temperature range (such as 40℃-60℃). Dynamically starting energy supply avoids the microstructure defects caused by energy excess in traditional steam curing, such as temperature stress and uneven hydration, significantly improves energy efficiency, and ensures quality uniformity.

[0112] When the core temperature inside the component embryo reaches the highest preset value (such as 65℃) and starts to stabilize or slowly decrease, it indicates that the most intense stage of hydration reaction has passed, and the concrete has a preliminary skeletal structure. The temperature oscillation cycle program is started. By controlling the heating and cooling units, the core temperature of the concrete is periodically fluctuated within a set range, such as between 55℃-65℃, each cycle lasting for several hours, so that the unhydrated particles in the micro voids are rearranged and contacted, promoting further hydration and improving density; and releasing the internal stress accumulated due to rapid heating, reducing the risk of later cracking.

[0113] When the inside humidity of the component embryo is monitored to show a clear and continuous downward trend from the continuous saturation state, it indicates that the main body hydration reaction has been basically completed, and the curing cover is automatically switched to the drying mode. The humidifying unit is turned off, the dehumidifying unit is started, the high-humidity air in the curing cover is sucked out, moderate heating (below 60 DEG C) is carried out to reduce the relative humidity and improve the water evaporation efficiency, and at the same time, the curing cover slowly introduces low-humidity air treated by drying to discharge high-humidity air. Continue this process until the pre-embedded internal wireless temperature and humidity sensor shows that the internal humidity of the concrete and the external environment reach equilibrium, and the base component is obtained.

[0114] Demolding and trimming: the base component is demolded, online visual scanning is carried out on the base component during hoisting, defect data is obtained, and automatic trimming is carried out.

[0115] As shown in Figure 6 , the present application provides a demolding and trimming method;

[0116] Specifically:

[0117] All magnetic unit positioning units are cut off, the locking mechanism automatically releases the mechanical locking force according to the preset unlocking sequence, and sends a reverse signal to the micro-porous sealing strip to trigger the initial demolding;

[0118] The lifting appliance adsorbs the surface of the base component by negative pressure adsorption, the micro-porous array of the mold side wall sprays pulse airflow, and the base component is lifted away from the mold;

[0119] During the process of lifting the base component away from the mold, the type, size and three-dimensional coordinates of the base component defects are automatically identified and labeled through online visual scanning and comparison, and automatic trimming is carried out accordingly to obtain the prefabricated component.

[0120] It should be noted that the central control system sends instructions to all electromagnets as magnetic positioning units, cuts off the power supply, and unlocks the magnetic force; the locking mechanism (such as hydraulic lock) of the mold automatically releases the mechanical locking force according to the preset program in a specific order, such as unlocking the corner first and then the middle part of the symmetric part, so as to avoid damage to the component caused by mold deformation. The negative pressure is introduced into the micro-porous sealing strip in the self-sealing groove to release the pressure air therein, so that it shrinks and returns to the unexpanded state, releasing the sealing and clamping force of the parting surface.

[0121] The gantry crane with multi-chamber vacuum chuck is moved above the component and lowered, the vacuum chuck is in contact with the surface of the component, then the vacuum pump is started, negative pressure is generated in the cavity inside the chuck, and the component is firmly adsorbed. At the moment when the lifting appliance starts to lift the component, the central control system instructs the micro-porous array of the mold side wall to switch to the positive jet mode, the pulse electromagnetic valve controls the compressed air to be sprayed out from the micro-porous array in the form of pulse, forming an air cushion to assist the component to separate from the mold.

[0122] A visual scanning tunnel is set up on the path of the component from the mold to the quality verification test platform, which is internally provided with multiple groups of high-resolution industrial cameras (for surface color, texture defects), linear laser scanners (for three-dimensional topography, flatness defects). When the component is hoisted through the tunnel, the sensor is triggered, all visual equipment works synchronously, the complete image and three-dimensional point cloud data of the surface of the component are quickly collected from the top surface and multiple sides, and based on the machine learning model (image recognition algorithm), the scanning data results are automatically compared with the CAD digital model of the component to identify and label the type, size and three-dimensional coordinates of the defects. Then, according to the type, size and three-dimensional coordinates of the defects obtained by comparison, a six-axis robot carries corresponding finishing tools to automatically repair and obtain a prefabricated component. An acoustic emission sensor array is arranged on the surface of the prefabricated component.

[0123] Quality verification and storage: The prefabricated component is subjected to compressive strength test and durability test, and the prefabricated component that passes the verification is intelligently stored.

[0124] As shown in Figure 7 , the application provides a quality verification and storage method;

[0125] Specifically:

[0126] Real-time monitoring of the dynamic response signal of the prefabricated component, analysis of the uniformity and activity of the internal structure change, and calculation of the compressive strength of the prefabricated component;

[0127] Scanning the surface of the prefabricated component, evaluating the difficulty of water molecules entering the surface layer of the prefabricated component, and obtaining a permeability index; comparing the permeability index with the predicted value of the key durability index to obtain durability evaluation data;

[0128] The prefabricated component that passes the quality verification is stored in a three-dimensional storage site provided with an adaptive support table; information management is performed through an electronic tag, and the prefabricated component is automatically vertically stored and taken out according to instructions.

[0129] It should be noted that in the process of hoisting the prefabricated component to the quality verification test platform, the elastic wave signals released by the internal micro cracks of the prefabricated component under stress are collected in real time through the uniformly arranged acoustic emission sensor array on the surface of the prefabricated component. Real-time analysis of acoustic emission signal energy, amplitude, impact number and other parameters, and use of sensor array time difference positioning technology to draw a time-space distribution map of acoustic emission events and identify damage active areas. The extracted acoustic emission characteristic parameters such as cumulative energy, event rate, and positioning cluster activity are input into the pre-trained machine learning prediction model to intelligently predict the compressive strength value of the prefabricated component; the model is trained based on a large number of historical sample data, which comes from: in the new product, new formula or new process verification stage, the corresponding data of destructive test and acoustic emission monitoring of specially made test blocks under the same conditions; from the production line, periodically or sample part of the prefabricated component, the corresponding data of destructive verification test and its acoustic emission data; the model learns a large number of the above two types of data to establish a reliable mapping relationship between acoustic emission characteristics and compressive strength. Then analyze the uniformity of acoustic emission events in the prefabricated component, and evaluate the compactness and defect condition of the internal structure.

[0130] A high-resolution infrared thermal imager is used to quickly scan the surface of the prefabricated component, and by analyzing the dissipation rate of surface temperature / evaporation heat, the rate and depth of water molecules invading the surface layer of the component are quantitatively evaluated, and a permeability index is calculated. The index directly reflects the core indicator of concrete durability, namely the anti-permeability ability. The calculated permeability index is input into the durability prediction model based on a large number of experimental data to output the predicted values of key durability indicators such as chloride ion diffusion coefficient and carbonation depth. Then automatically compare these predicted values with the threshold values required by the design specification to obtain the durability evaluation data.

[0131] The precast component that fails the quality verification is explicitly marked to prevent confusion with qualified products, and is moved to the unqualified product area and crushed by a crusher; the crushed concrete blocks are screened to recycle the recycled aggregate and realize resource recycling. The precast component that passes the quality verification is pasted with an RFID electronic tag, which stores the unique ID, production date, strength grade, durability data, geometric size and other identity information of the precast component, and is stored in an automated warehouse, each storage location of which is provided with a gantry with a multi-degree-of-freedom adjustable support arm. After receiving the instruction, the warehouse management system controls the RFID reader / writer on the stacker to automatically identify the target precast component, and vertically and efficiently stores or takes out the target precast component from the specified storage location. When the precast component is transported from the quality inspection test platform to the storage location by the stacker, the pressure sensor array on the support table senses the shape and weight distribution of the component, and automatically adjusts the height and angle of each support arm to ensure that the precast component is always in the best stress state, and avoid cracking caused by internal stress generated by long-term storage. The warehouse is also equipped with temperature and humidity sensors to ensure that the storage environment is stable and prevent unnecessary dry shrinkage or moisture absorption of the component before use.

[0132] The control group and the experimental group are set up, and the high-performance concrete precast components are prepared by using the prior art method and the method of the present application respectively. The control group and the experimental group are designed for the mixing ratio of the concrete with the strength grade of C50, and each group prepares 10 precast components with the size of 100mm*100mm*400mm. The homogeneity, strength, yield rate and durability of the two methods are compared, and the final data is the average value, as shown in Table 1.

[0133] Table 1 Comparison of performance of high-performance concrete precast components prepared by the present application and the prior art

[0134]

[0135] Therefore, it can be seen that, by using the step-by-step mixing, synergistic degassing and dynamic curing and other innovative processes, the homogeneity of the concrete, the yield rate of the component demolding, and the compressive strength and durability of the component are significantly improved under the premise of using recycled raw materials.

[0136] Although the embodiments of the present application have been shown and described, it can be understood by those of ordinary skill in the art that various changes, modifications, replacements and variations can be made to the embodiments without departing from the principles and spirits of the present application, and the scope of the present application is defined by the appended embodiments and their equivalents.

Claims

1. A process for the production of high performance concrete precast elements, characterized in that, The method comprises the following steps: Raw material preparation: according to the mixing ratio, the solid waste-based cementitious material, recycled aggregate, fiber, water reducing agent and mixing water are weighed, and the raw materials are pretreated; Mold preparation: according to the design drawing of the prefabricated component, the mold base is made, and the polytetrafluoroethylene composite coating is uniformly applied; Install and fix the embedded parts, close and lock the mold; Mixing and quality control: prepare homogeneous slurry and wet aggregate bed, inject the slurry into the wet aggregate bed, homogenize to obtain concrete mixture, and test the performance of the concrete mixture; Pouring: pour the concrete mixture into the mold, and extrude, scrape and recycle the excess material by the profiling press plate to obtain the component embryo; Curing: dynamically respond to the state of the concrete hydration reaction through the intelligent curing cover, supply energy on demand, oscillate and strengthen, and close-loop dry to obtain the base component; Demolding and trimming: demold the base component; scan the base component during hoisting to obtain defect data, and automatically trim to obtain the prefabricated component; Quality verification and storage: test the compressive strength and durability of the prefabricated component, and store the verified prefabricated component intelligently.

2. The process for preparing a high performance concrete precast member according to claim 1, characterized in that: The pretreatment method of the raw materials comprises the following steps: S1, microwave-chemical compound impurity removal and microbial mineralization repair of recycled aggregate; S2, magnetic field pre-orientation arrangement and plasma oil removal and roughening of fiber; S3, synergistic thermalization and countercurrent chromatography enrichment of key components of solid waste-based cementitious material.

3. The process for manufacturing high performance concrete precast elements according to claim 1, characterized in that: The contents of the mold preparation step include: M1, make a mold base integrated with a magnetic positioning unit, a self-sealing groove and an optical calibration base point, and process a vacuum micro-hole array on the working surface of the mold base; M2, based on the physical mask method, selectively sinter the polytetrafluoroethylene composite coating on the working surface, remove the physical mask after the coating is cooled and solidified; M3, clean the mold, and automatically scan the surface state of the polytetrafluoroethylene composite coating and the size of the mold, while checking whether the vacuum micro-hole array is unblocked and free from blockage; M4, place the embedded parts in the magnetic grid, and automatically adsorb and lock them by magnetic force; M5, close the mold, trigger the expansion of the sealing strip in the self-sealing groove to realize self-sealing, automatically read the optical reference point to check the closing accuracy, test the sealing integrity by vacuumizing, and obtain the mold finished product.

4. The process for manufacturing high performance concrete precast elements according to claim 1, characterized in that: The mixing and quality control step comprises: N1, high-speed shearing stirring of solid waste-based gel material, water reducing agent and part of water to obtain homogeneous slurry; N2, stirring of recycled aggregate and remaining water to obtain uniform wet aggregate bed; N3, injection of slurry into the stirring wet aggregate bed by pressurized injection; N4, after all the homogeneous slurry is injected into the wet aggregate bed, short-time high-efficiency homogenization stirring is carried out to obtain concrete mixture with uniform distribution of components; N5, perform slump test and unit weight test on the concrete mixture, and adjust the process according to the test results.

5. The process for manufacturing a high performance concrete precast element according to claim 1, characterized in that: The contents of the pouring step include: P1, the concrete mixture is injected through a movable nozzle, closely fills the surface and is uniformly injected along a preset path, and fibers are added; meanwhile, a directional energy field is applied above the filling surface to reduce the apparent viscosity of the concrete, and a vacuum is applied in the micropores of the side wall area of the mold that has not been filled to discharge the internal bubbles of the concrete; P2, the filling height in the mold is monitored in real time, and the injection is stopped when the preset filling height is reached; an intelligent pressing plate with a profiling structure is used to press and flatten the surface to the design elevation, and the excess material is cut off and recycled; P3, the vacuum state is maintained, the vacuum degree change is monitored, the internal structure is confirmed to be stable, and the surface is automatically scanned to confirm that there is no bleeding phenomenon and no bubble overflow, and the component embryo is obtained.

6. The process for preparing a high performance concrete precast element according to claim 5, characterized in that: The vacuum applied in the micropores of the side wall area of the mold that has not been filled is linked with the position of the movable nozzle, so that the vacuum always acts on the gas-material interface front.

7. The process for manufacturing a high performance concrete precast element according to claim 1, characterized in that: The contents of the curing step include: Q1, cover the component embryo with a closed intelligent curing cover, and perform initial static stopping; Q2, the core temperature and humidity of the component embryo are monitored in real time, and the directional energy supply is dynamically started; Q3, when the core temperature reaches the preset value and tends to be stable, temperature oscillation cycle is adopted to optimize the internal microstructure of the component embryo, and early strength is obtained; Q4, according to the real-time humidity data, automatically switch to the drying mode until the internal humidity of the component embryo is balanced with the outside, and the base component is obtained.

8. The process for manufacturing a high performance concrete precast element according to claim 1, characterized in that: The contents of the demolding and trimming step include: R1, cut off the magnetic force of all magnetic unit positioning units, the locking mechanism automatically releases the mechanical locking force according to the preset unlocking sequence, and sends a reverse signal to the micropore sealing strip to trigger the initial demolding; R2, the lifting appliance adsorbs the surface of the base component by negative pressure adsorption, and the micropore array of the mold side wall sprays pulse airflow, and the base component is lifted away from the mold; R3, during the process of lifting the base component away from the mold, the type, size and three-dimensional coordinates of the defects of the base component are automatically identified and labeled through online visual scanning and comparison, and automatic trimming is performed accordingly, and the prefabricated component is obtained.

9. The process for manufacturing a high performance concrete precast element according to claim 1, characterized in that: The contents of the quality verification and storage step include: G1, the dynamic response signal of the prefabricated component is monitored in real time, the uniformity and activity of the internal structure change are analyzed, and the compressive strength of the prefabricated component is calculated; G2, the surface of the prefabricated component is scanned, the difficulty of water molecules entering the surface layer of the prefabricated component is evaluated, and the permeability index is obtained; the permeability index is compared with the predicted value of the key durability index to obtain durability evaluation data; G3, the prefabricated component that passes the quality verification is stored in a three-dimensional storage site provided with an adaptive support table; information management is performed through an electronic tag, and the prefabricated component is automatically vertically stored and taken out according to the instructions.

Citation Information

Patent Citations

  • Manufacturing process of high-performance concrete prefabricated part

    CN120116318A